Crecimiento y Desarrollo vegetativo de arándano (Vaccinium corymbosum L. var. Biloxi) en tres pisos altitudinales de la provincia de Loja. - Lima Balcázar, Andreina Mariela (2019)
Cranberry farming (Vaccinium corymbosum L.) is having a world exponential growth. Even though, research in the tropics started a few years ago, the knowledge of its development under the conditions of our country is still unclear. There are some studies about the growth of Biloxi variety under different conditions showing more growth at a lower altitude, but associated to the replacement of the requirements this variety was developed with in its initial habitat. That is why the need to study Biloxi variety development and growth appears, which has been liberated and used under different conditions, showing a good adaptation in the tropics zones, due to its precociousness. The objective of this research was to evaluate the vegetative growth and development of Biloxi variety. It was settled on three different altitudinal floors in Loja province, under open field conditions with a homogeneous treatment until the end of the test. This is why the field phase was carried out on three altitudinal floors in Loja city, which belongs to Loja canton at 2 141 m. a. s. l., in Landangui Neighborhood, Malacatos parish which belongs to Loja canton at 1 555 m. a. s. l., and in Zapotepamba Neighborhood Casanga parish which belongs to Paltas canton at 900 m. a. s. l., during a period of four months (October 2018 – February 2019) under a DCA arrangement with three treatments and fifteen repetitions. Inside the measures the following variables were registered: plant height, coverage, number of stems, length of sprout, number of the sprout brooms, TCA and TCR of the sprout length and diameter, foliar area of the sprout and IAF. In order to observe the relationship with the growth rates, Relative Humidity and Effective Temperature were considered as well. As part of the results, until the end of this research the treatments did not present a meaningful growth in relation with the height, length of the sprout, number of stems and brooms. However, Loja treatment showed a significance in relation with the foliar area of the sprout and IAF. The temperature had an influence in Landangui and Zapotepamba treatment in relation with the analysis of the growth rates. Key words: Biloxi variety, altitudinal floors.